Safe, Green, and Efficient Synthesis of m‐Dinitrobenzene via Two‐Step Nitration in a Continuous‐Flow Microreactor. Issue 14 (12th April 2023) - Zhao, Wenyuan; Zhang, Qi; Wei, Wei; Xu, Weichang; Sun, Wenxuan; An, Tingwang; Ji, Lu; Wang, Hande; Zhou, Chuan; Yan, Dongmao
Abstract: In industry, m‐dinitrobenzene is mainly obtained by two‐step nitration of benzene, but still faces the problem of being heterogeneous and highly exothermic. In this work, a two‐step continuous‐flow nitration was developed in a microreactor, combining benzene nitration and mononitrobenzene nitration in series. The waste acid after the mononitrobenzene nitration stage was utilized in the benzene mononitration stage, and the waste acid in the benzene mononitration stage was treated and concentrated for reuse. The whole process consumes almost no sulfuric acid. Under optimal conditions, the yield of dinitrobenzene was more than 99.0 % and the selectivity of m‐dinitrobenzene was more than 91 % with a residence time of 4 min at 70 °C. In addition, the space‐time yield of the continuous microreactor was 800 times higher than the batch reactor. It provides a safe and efficient method for the industrial production of m‐dinitrobenzene. Abstract : A continuous flow microreactor process was developed to produce m‐dinitrobenzene by two‐stage nitrification on a kilogram scale. The process realized the recycling of waste acid with almost no sulfuric acid consumption. In addition, the process has milder conditions and higher production efficiency.